Social Stratification in an Aging Society with Low Fertility The Case of Japan - Shirahase, Sawako (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This edited book discusses stratification in contemporary Japanese society. It is unique for its empirical examination of social inequality in relation to declining fertility and an aging population. Japan is the most aged society in the world: according to the Statistics Bureau of Japan, people who are aged 65 and above accounted for 29.1% of the country's total population in 2021. Meanwhile, the fertility rate has continuously declined since the mid-1970s. Japan experienced a dramatic change in its demographic structure in a short period of time. Such fast change could be a major factor in generating social stratification. In her industrialization, Japan was thought to share a pattern of social stratification similar to that of developed European and North American countries but with a low degree of socio-economic inequality and a high degree of homogeneity. There is no clear support for this description of Japan, although the country does share a pattern and degree of social stratification similar to that observed in Europe and North America. The social stratification theory has been developed in close relation to the labor market; however, it is necessary to further examine the social stratification of very aged societies in which a substantial number of the population-namely, retired persons-no longer have any ties to the labor market. In this book, the contributors explore the pattern of social stratification at three life stages: young, middle-aged, and elderly. Included are discussions of various aspects of stratification such as education, work, wealth, marriage, family, gender, generation, and social attitudes. Sawako Shirahase is Professor of Sociology at the Graduate School of Humanities and Sociology, The University of Tokyo.
Chapter 1 Class Structure, Education, and Social Mobility in Post-war Japan -- Chapter 2 The changing marriage market and status homogamy -- Chapter 3 Relative Indices of Educational Attainment and Trend Analysis of Inequality of Educational Opportunity Using the 2015 SSM Survey Data -- Chapter 4 Long-Term Trends in Long-Term Employment in Japan -- Chapter 5 Intragenerational Mobility between Regular and Non-regular Employment Sectors in Japan: From the Viewpoint of the Theory of Mobility Regime -- Chapter 6 Gap in Attitudes toward Higher Education between Graduates and Non-graduates: Growing Educational Disparity in Younger Cohorts -- Chapter 7 Effects of Regional Inequality on Political Attitudes: Social Capital and Support for Redistribution and Free Competition -- Chapter 8 Explanation of Socioeconomic Inequality among the Male Elderly: An Approach Based on Estimated Income History -- Chapter 9 Another aspect of social inequality, wealth, in a super-aged society, Japan: Re-examining the conventional framework of social stratification.
Keywords: Microeconomics; Social structure; Equality; Sociology; Social groups; Demography; Population; Social policy; Microeconomics; Social Structure; Sociology of Family, Youth and Aging; Population and Demography; Social Policy